Eighth Five Year Plan (1992-97) and Annual Plan 1995-96 (Draft) Jammu and Kashmir - Planning Commission (Planning Commission, 1992)
The Eighth Five Year Plan of Jammu and Kashmir State envisaged a total investment of Rs. 4000 crores. This included a component of about Rs. 1800 crores as the spill over cost of continued schemes. The major effort envisaged in the Eighth Plan is to harness the State's potential in different fields to achieve the ultimate goal of self sustaining economy.
Planning and Development Department, Jammu and Kashmir